2017
DOI: 10.1016/j.jvs.2016.06.109
|View full text |Cite
|
Sign up to set email alerts
|

Few internal iliac artery aneurysms rupture under 4 cm

Abstract: IIAA is an uncommon condition and mostly coexists with other aortoiliac aneurysms. Follow-up until a diameter of 4 cm seems justified, at least in elderly men, although lack of surveillance data precludes firm conclusions. The mortality was low compared with previously published figures and lower than mortality in patients with ruptured abdominal aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 23 publications
0
36
0
3
Order By: Relevance
“…In Finland, 8 per cent of ruptured AAAs were below 55 mm in diameter 18 . In a multinational study 19 , 6 per cent of IIAAs were smaller than 40 mm at the time of rupture. Thus, factors other than size influence the risk of rupture.…”
Section: Discussionmentioning
confidence: 95%
“…In Finland, 8 per cent of ruptured AAAs were below 55 mm in diameter 18 . In a multinational study 19 , 6 per cent of IIAAs were smaller than 40 mm at the time of rupture. Thus, factors other than size influence the risk of rupture.…”
Section: Discussionmentioning
confidence: 95%
“…The development and growth of aneurysms involve the complex events of arterial wall cells remodeling (38). Previous studies have demonstrated that apoptosis is involved in the pathogenesis of aneurysms (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Laine et al. [ 5 ] suggest that a 40-mm threshold for elective treatment might be quite safe, due to low incidence of rupture in IIAA <40 mm.…”
Section: Discussionmentioning
confidence: 99%